2007
DOI: 10.1358/mf.2007.29.1.1063489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the modulatory role of nimodipine in seizures with kainic acid and pentylenetetrazole

Abstract: The present study aimed at establishing the CD50 and CD99 doses along with complete dose-response profile of two convulsants, namely, kainic acid and pentylenetetrazole (PTZ), in mice and evaluating the modulatory role of the cerebroselective dihydropyridine calcium channel blocker nimodipine. Kainic acid and PTZ were administered intraperitoneally in a dose range of 1-30 mg kg(-1) and 35-75 mg kg(-1), respectively. Nimodipine was administered in graded doses (1-8 mg kg(-1), i.p.) with 15 min pretreatment time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In the present study PTZ was used to induce convulsions owing to the role of calcium ion as a common mediator in PTZ-induced convulsions [22]. This model was suitable for testing our hypothesis that the anti-convulsant activity of B. diffusa roots might be due to calcium channel blocking effect by liriodendrin.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study PTZ was used to induce convulsions owing to the role of calcium ion as a common mediator in PTZ-induced convulsions [22]. This model was suitable for testing our hypothesis that the anti-convulsant activity of B. diffusa roots might be due to calcium channel blocking effect by liriodendrin.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a role of Ca 2+ in epileptogenesis has been shown in hippocampal slices and cultured hippocampal neurons [35], [36]. Furthermore, pharmacological studies on anticonvulsant properties of Ca 2+ antagonists in mouse have provided a direct link between Ca 2+ channel function and susceptibility to PTZ-induced seizures [37]. Concerning the pharmacological actions of PF, it was reported that PF treatment suppressed the [Ca 2+ ] i elevation induced by glutamate stimulation in rat pheochromocytoma (PC12) cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Altered Ca2+ removal rate was also reported for animal models for epilepsy (Pal et al., 2001; Raza et al., 2001). Furthermore, pharmacologic tests with antiseizure properties of Ca 2+ antagonists and genetic mouse models have provided a direct link between Ca 2+ channels and PTZ‐induced seizure activity (Weiergräber et al., 2006; Shitak et al., 2007). Following the influx, calcium is being removed from the cell via an ATP‐dependent calcium transporter.…”
Section: Discussionmentioning
confidence: 99%